A model for supersaturation and aspect ratio for growth dominated crystallization from solution. Issue 12 (22nd August 2015) - Derdour, Lotfi; Chan, Eric J.
Abstract : A model for predicting supersaturation, crystal growth rate, crystal size distribution, and aspect ratio is presented. The model applies to isothermal anti‐solvent crystallization where crystal growth is the dominant phenomena and for systems where crystal habit can be characterized by two‐dimensional variables. A parameter estimation algorithm was derived to extract solute integration coefficients in the two growth directions from experimental data about temporal evolution of concentration during crystallization, the final aspect ratio, and the aspect ratio at the end of the seed age period. Model's predictions for supersaturation and aspect ratio were in good agreement with experimental data obtained on an investigational drug that crystallizes in the parallelepipedic shape. Finally, model simulations predict that for a given initial seed size, the seed loading is the main factor impacting the final aspect ratio and thus identified the range of seed loading that would result in undesired powder flow. © 2015 American Institute of Chemical Engineers AIChE J, 61: 4456–4469, 2015